Co-Doped Magnesium Oxychloride Composites with Unique Flexural Strength for Construction Use - Lauermannová, Anna-Marie; Jankovský, Ondřej; Lojka, Michal; Faltysová, Ivana; Slámová, Julie; Pavlíková, Milena; Pivák, Adam; Marušiak, Šimon; Pavlík, Zbyšek; Záleská, Martina (Materials (Basel, Switzerland), 2022)
In this study, the combined effect of graphene oxide (GO) and oxidized multi-walled carbon nanotubes (OMWCNTs) on material properties of the magnesium oxychloride (MOC) phase 5 was analyzed. The selected carbon-based nanoadditives were used in small content in order to obtain higher values of mechanical parameters and higher water resistance while maintaining acceptable price of the final composites. Two sets of samples containing either 0.1 wt. % or 0.2 wt. % of both nanoadditives were prepared, in addition to a set of reference samples without additives. Samples were characterized by X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy, and energy dispersive spectroscopy, which were used to obtain the basic information on the phase and chemical composition, as well as the microstructure and morphology. Basic macro- and micro-structural parameters were studied in order to determine the effect of the nanoadditives on the open porosity, bulk and specific density. In addition, the mechanical, hygric and thermal parameters of the prepared nano-doped composites were acquired and compared to the reference sample. An enhancement of all the mentioned types of parameters was observed. This can be assigned to the drop in porosity when GO and OMWCNTs were used. This research shows a pathway of increasing the water resistance of MOC-based composites, which is an important step in the development of the new generation of construction materials.
Keywords: co-doped magnesium oxychloride cement; mechanical and physical parameters; microstructure; morphology and phase composition; graphene oxide; oxidized MWCNTs